2016
DOI: 10.1177/2049463716668904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding intrathecal morphine to a multimodal analgesic regimen for postoperative pain management after laparoscopic bariatric surgery: a prospective, double-blind, randomized controlled trial

Abstract: The addition of IT morphine to a multimodal analgesic regimen after laparoscopic bariatric surgery was an effective and safe method that markedly reduced postoperative pain, systemic opioid consumption and length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…However, as many as 15 patients from group B asked for additional analgesia after the first hour and they received 2-5 mg of morphine chloride intravenously. The average consumption of morphine chloride after 24 hours was 21.7 mg in group B, which confirms the statement made by El Sherif et al [20] who claimed that intrathecal morphine has about 100 times more potency than intravenous morphine. Jacobson et al [21] believed that intrathecally administered morphine yields effective long-lasting analgesia (over 20 hours) and that the dose from 0.3 mg to 1 mg should ensure good analgesia without the major complication -respiratory depression.…”
Section: Discussionsupporting
confidence: 87%
“…However, as many as 15 patients from group B asked for additional analgesia after the first hour and they received 2-5 mg of morphine chloride intravenously. The average consumption of morphine chloride after 24 hours was 21.7 mg in group B, which confirms the statement made by El Sherif et al [20] who claimed that intrathecal morphine has about 100 times more potency than intravenous morphine. Jacobson et al [21] believed that intrathecally administered morphine yields effective long-lasting analgesia (over 20 hours) and that the dose from 0.3 mg to 1 mg should ensure good analgesia without the major complication -respiratory depression.…”
Section: Discussionsupporting
confidence: 87%
“…The postoperative pain score was evaluated by a visual analog scale (VAS) score, 16 where 0 means no pain and 10 means severe pain. VAS scores were measured at 2, 4, 6, and 24 hours after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Sleep variables, such as sleep efficiency (the ratio of total sleep time/total recording time), the Athens insomnia scale (AIS) subjective sleep quality, the percentage of REM sleep, Unstable sleep and Stable sleep were recorded and analyzed by sleep laboratory staff who was blinded to patients' information. Postoperative pain scores were evaluated by Visual analogue scale (VAS) score,12 which indicated that 0 was considered painless, and a score of 10 was considered as intense pain. Scores of 4 and below were considered mild pain (pain does not affect sleep), and scores of 5 to 6 were considered moderate pain (pain influences sleep, but the patients can still fall asleep).…”
Section: Methodsmentioning
confidence: 99%